Produksi Etil Ester Dari Minyak Dedak Padi (Oryza Sativa) Menggunakan Reaktor Ultrasonik - Aisyah Aisyah; Riskayanti Riskayanti; Iin Novianty; Asriyani Ilyas; Sjamsiah Sjamsiah; Sitti Chadijah (Al-Kimia, 2018)
Indonesia as the third largest grain producer in the world produces large amounts of bran. High contain Free Fatty Acid (FFA) in rice bran oil causes it can be converted into the fatty acid ethyl esters (biodiesel) by esterification and transesterification methods. The rice bran oil was obtained by rice bran extraction using n-hexane. The esterification process was catalyzed by HCl. In this study, the transesterification process to convert triglycerides into ethyl esters (biodiesel) was conducted by the addition of KOH as a neutralizer and a catalyst Oil and ethanol by ratio 1:6 using 0,5% KOH  as catalysator were reacted by utilizing 47 kHz ultrasonic wave for 45, 60 and 75 minutes. Biodiesel conversion value obtained were 49,23%; 70,55% and 52,04% respectively. Biodiesel product spectrum was analyzed using FTIR and GCMS instrument. The density, viscosity and flash point is also measured.  FTIR analysis on all variations give similar data spectrum, where the ethyl ester products are characterized by typical bands at specific frequencies such as -C=O; -C-C; -C-H (sp3) and = C-H (sp2) stretch. Based on the data from GCMS spectrum, the product components are ethyl palmitate, ethyl linoleate, ethyl stearate and ethyl oleate.